Prática alimentar materna de restrição para controle de peso do filho e características associadas - Freitas, Fabricia Ramos de [UNIFESP] (2017)
Background: Obesity is a widely discussed topic in the scientific literature because of the serious consequences of this public health disease. Studies on family dynamics observation and parental feeding practices offer valuable information on the subject by pointing to parental attitudes as one of the main factors associated with excessive weight gain and obesogenic behavior in children. The results of these investigations provide evidences on the importance of feeding strategies adopted by parents in relation to child’s feeding, especially those associated with the regulation of the quality and quantity of the foods consumed. Restriction is the most widely investigated feeding practice with the primary goal of controlling child’s food intake. Studies have shown that parental restriction is related to child’s overweight and may lead to a decreased ability of the child in relation to food selection, preferences and self-control of food intake, especially due to the interference in their perception of internal signs of hunger, satiety and regulation of appetite. It is important to emphasize that the study of parental feeding practices is scarce in the Brazilian literature and, in this way, the present study aimed to contribute to the knowledge of the subject in the Brazilian population. Objective: Investigate the association between mothers' use of restriction for child’s weight control and the socioeconomic, demographic, behavioral, dietary and anthropometric characteristics of parents and their child. Methods: Nine hundred and twenty seven mothers of children aged 2 to 8 years enrolled in private schools in the cities of São Paulo and Campinas completed the Brazilian version of the Comprehensive Feeding Practices Questionnaire, which was used to measure maternal restriction for child weight control. Additionally, mothers reported their responsibility and concern about child feeding, as well as other parent and child characteristics. For data analysis, descriptive, univariate and multiple logistic regression analyzes were performed. Results: The analysis of maternal characteristics revealed a high level of schooling among the studied population, less than one quarter of the mothers reported incomplete upper level (11.43%) and about one third were overweight (29.26%). Considering children's characteristics, almost half of the children (49.03%) consumed ultraprocessed foods in the seven days prior to the survey, and although 30% of the children were classified as having excessive weight, only 6% of the mothers perceived them as slightly fat / fat.The multiple logistic regression model revealed that maternal restriction to control child's weight was independently associated with the perception that her child is a little fat / fat / very fat (OR = 4.61, p = 0.001), concern about overweight in children (OR = 2.61, p <0.001), with child’s weight, i.e. overweight/ obesity / severe obesity (OR = 2.18, p <0.001) and child’s consumption of ultraprocessed foods (OR = 1.40, p = 0.026). Conclusion: Although restriction is an alternative for mothers to promote healthy eating habits and to control their children's weight, such practice can be harmful to child's physical and emotional health and should not be encouraged. Intervention programs should assist in raising parents' awareness of their children's weight status and should involve recommendations that include building a flexible environment in which children are encouraged to participate in the choice of foods they eat.